2022
DOI: 10.46743/2160-3715/2022.5432
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Hybrid Learning for Students with Learning Disabilities in Primary Schools Providing Inclusive Education

Abstract: Many special-needs children, including students with learning disabilities, are enrolled in public schools. The current state of education is transitioning from online to face-to-face learning due to the improving situation after the COVID-19 pandemic. Hybrid learning is one of the alternative methods applied during the transition period. Therefore, this study aims to explore the experiences of teachers in implementing hybrid learning in students with disabilities in Indonesia using a qualitative description. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…Furthermore, the effectiveness of using media to support learning success has been supported both theoretically and empirically. Previous studies found the importance of using media in learning to read in dyslexia students (Zid et al, 2020;Zid and Casmana, 2021;Rachmawati et al, 2022). Rachmawati et al (2022) also proved the importance of using visual and real media as well as a multisensory approach in supporting the success of learning to read.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Furthermore, the effectiveness of using media to support learning success has been supported both theoretically and empirically. Previous studies found the importance of using media in learning to read in dyslexia students (Zid et al, 2020;Zid and Casmana, 2021;Rachmawati et al, 2022). Rachmawati et al (2022) also proved the importance of using visual and real media as well as a multisensory approach in supporting the success of learning to read.…”
Section: Discussionmentioning
confidence: 80%
“…Previous studies found the importance of using media in learning to read in dyslexia students (Zid et al, 2020;Zid and Casmana, 2021;Rachmawati et al, 2022). Rachmawati et al (2022) also proved the importance of using visual and real media as well as a multisensory approach in supporting the success of learning to read. The method supports the effectiveness of learning outcomes, namely to arouse the interest of students and facilitate their understanding of the concepts.…”
Section: Discussionmentioning
confidence: 80%
“…(Mushtaha et al, 2022) The most significant advantage of online learning implementation was flexibility. Sudden implementation had discouraging implications for mental health and socialization (Rachmawati et al, 2022) Post COVID-19, hybrid learning is used as an alternative method. Teachers support hybrid learning for students with learning disabilities in inclusive classes by providing clear instructions, reducing anxiety in online spaces, special assistance, and adaptive learning media.…”
Section: Charting the Datamentioning
confidence: 99%
“…e-ISSN: 2715-5706 menunjukkan bahwa penggunaan media pembelajaran adaptif disertai pendampingan guru mendukung keberhasilan pembelajaran hybrid bagi siswa berkesulitan belajar di kelas inklusi (Rachmawati et al, 2022). Di samping itu, dengan menggabungkan teknologi imersif yang sesuai dengan teori pembelajaran motorik dan prinsip pembelajaran multimedia, materi pembelajaran yang sesuai dapat dibuat yang memfasilitasi proses pembelajaran fisik bagi penyandang disabilitas (Mokmin & Ridzua, 2022).…”
Section: Paper | 721unclassified